P60 How can mentoring programmes for young people in secondary schools in the united kingdom be classified? developing a typology using qualitative methods. (2nd September 2017) - Busse, H; Campbell, R; Kipping, R
Abstract : Background: Despite a lack of robust evidence of effectiveness, mentoring programmes are commonplace in various settings and contexts in the United Kingdom (UK). Due to their potential to influence health and educational outcomes, it is of public health interest to obtain a better understanding of the types of mentoring programmes currently available to comprehend what 'mentoring' means and to aid the evaluation of such programmes. The aim of this study was to develop a typology of currently active mentoring programmes that provide formal mentoring for young people in UK secondary schools. Methods: Eight websites were searched to retrieve details of UK organisations that provide mentoring programmes for young people. Maximum variation sampling based on country and the type of mentoring programme was used to include a variety of different programmes. Programme managers from purposefully selected organisations were invited to take part in semi-structured telephone interviews to obtain a thorough account of their mentoring programme(s). Interviews were facilitated using a topic guide and were audiotaped and transcribed verbatim. Thematic data analysis occurred iteratively to data collection and was facilitated using NVivo10 software. A framework matrix was established to compare programmes (cases) with categories derived from the analysis (codes) to aid the development of a typology. Results: Of 29 invited programme managers, 23 agreed to take part (79% response rate) and described a total of 28 mentoring programmes. The typology drawn from this work differentiates mentoring programmes by three overarching categories: mentoring programmes' overall aim and target group; type of mentor and mentoring programme setting. These categories each have a range of sub-categories. Based on different combinations of these sub-categories, 12 'mentoring models' were identified within two broad groupings of 'personal and developmental' and 'educational and employability' mentoring programmes. Conclusion: Although mentoring programmes are heterogeneous, it is possible to identify key characteristics and distinguish between different models. Using semi-structured telephone interviews allowed for a thorough investigation of differences between mentoring programmes that was grounded in participants' accounts of their programmes. The typology enables mentoring programmes to be categorised into one of 12 'mentoring models'. A future study is needed to test the typology's generalisability in the UK. Such a typology can help us to understand what is being delivered, for whom, and how, which is a necessary precursor to any public health evaluation.